2022
DOI: 10.1186/s12876-022-02594-2
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal microRNAs in the DLK1-DIO3 imprinted region derived from cancer-associated fibroblasts promote progression of hepatocellular carcinoma by targeting hedgehog interacting protein

Abstract: Background Hepatocellular carcinoma (HCC) is the sixth most commonly diagnosed cancer and third leading cause of cancer-related death worldwide in 2020. Exosomes derived from cancer-associated fibroblasts (CAFs-exo) can promote tumor progression in various human cancers. However, the underlying regulatory mechanism controlling how CAFs-exo can promote HCC progression remains poorly understood. Methods CAFs and para-cancer fibroblasts (PAFs) were is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…miRNAs in the DLK1-DIO3 imprinting area, including miR-329-3p, miR-380-3p, miR-410-5p, and miR-431-5p, were found to be upregulated in hepatocellular carcinoma (HCC) cells co-cultured with exosomes produced from CAFs. These miRNAs inhibited HHIP expression, weakened cell adhesion, and enabled cell migration and invasion ( Jin et al, 2022 ). In HCC, miR-20a-5p has been demonstrated to have a comparable impact ( Qi et al, 2022 ).…”
Section: Function Of Caf-derived Exosomal Mirna In Promoting Tumorige...mentioning
confidence: 99%
“…miRNAs in the DLK1-DIO3 imprinting area, including miR-329-3p, miR-380-3p, miR-410-5p, and miR-431-5p, were found to be upregulated in hepatocellular carcinoma (HCC) cells co-cultured with exosomes produced from CAFs. These miRNAs inhibited HHIP expression, weakened cell adhesion, and enabled cell migration and invasion ( Jin et al, 2022 ). In HCC, miR-20a-5p has been demonstrated to have a comparable impact ( Qi et al, 2022 ).…”
Section: Function Of Caf-derived Exosomal Mirna In Promoting Tumorige...mentioning
confidence: 99%
“…CAFs derived exosomes could also dramatically elevate the rates of intrahepatic and pulmonary metastasis of HCC. Jin et al (138), demonstrated that exosomes separated from CAFs could be absorbed by HCC cells and accelerated their invasive phenotype compared with para-cancerous fibroblasts (PAFs), and mechanistic experiments revealed that CAFs could offer multiple miRNAs (miR-329-3p, miR-380-3p, miR-410-5p, miR-431-5p) were delivered to HCC cells and increased their expression levels. Additionally, downregulation of LIMA1 expression was associated with poor OS and recurrence-free survival (RFS) in HCC patients.…”
Section: Crosstalk Between Hcc and Cafsmentioning
confidence: 99%